More Innovation, Less Poverty-Stricken: A Case of Rural Youth Activism in Trenggalek, Indonesia: - Dedo Ari Setiawan; Astuti, Eka Zuni Lusi (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2023)
The COVID-19 pandemic has evoked collective anxiety among rural populations due to social restrictions that have caused disruptions to local education and industries. This article delves into the intricate social innovations undertaken by Ikatan Sedulur Trenggalek [Trenggalek Brotherhood] in its endeavors to address the multifaceted challenges of poverty amid the backdrop of pandemic. IST as a prominent constituent of Trenggalek civil society assumes a pivotal role in the realm of rural humanitarian affairs and the provision of robust health support. This empirical investigation primarily seeks to illuminate the profound social programs orchestrated by astute youth members within this fraternal association, which have emerged as indispensable responses to the escalating urgency of poverty-related predicaments stemming from the pandemic. The analysis reveals that IST, as a rural youth-led civil society initiative, has undergone innovations and adaptations during the pandemic. The results highlight some of IST's principal programs, including the creation of a digital database for local individuals in need, ambulance services, voluntary initiatives, fund-raising programs, and institutional collaborations with rural entities and local institutions. This research strives to provide scholarly insights into the indispensable contributions of rural youth activism in ameliorating the plight of poverty during the tumultuous course of pandemic.